A feasible method to evaluate fetal palate: sequential sector-scan through oral fissure - Xiaofeng Lu; Yi Zhou; Min Fan; Wanyan Li; Chaoxue Zhang (BMC, 2023)
Abstract Background Prenatal diagnosis of cleft palate is still challenging. To describe a practical and efficient method, sequential sector-scan through oral fissure (SSTOF), to evaluate palate. Methods According to the characteristics of the fetal oral anatomy and ultrasonic directivity, we designed a practical method, sequential sector-scan through oral fissure, to evaluate the fetal palate, and the approach was verified efficiently by following up results of those fetuses with orofacial cleft who were induced because of their accompanied lethal malformations. Then, the 7098 fetuses were evaluated using sequential sector-scan through oral fissure. Fetuses were followed up after birth or induction to validate and analyze prenatal diagnosis. Result According to the scanning design, sequential sector-scan through oral fissure was performed successfully from the soft palate to the upper alveolar ridge in induced labor fetuses, and the structures were displayed clearly. Among 7098 fetuses, satisfactory images were obtained for 6885 fetuses and the remaining 213 fetuses' images were unsatisfactory because of fetuses' positions and pregnant women with high BMI. Among 6885 fetuses, 31cases were diagnosed CLP or CP, which were confirmed after delivery or termination. There were no missing cases. Conclusions SSTOF is a practical and efficient method to diagnose cleft palate, which might be applied to evaluate the fetal palate in prenatal diagnosis.